Self-concept clarity, academic self-efficacy, perceived social support and generalised pathological internet use among university students in Malaysia - Tam, Kheng Hung (2020)
Intensive use of the Internet among university students potentially leads to the development of generalised pathological Internet use (GPIU). Consistent with Davis's cognitive-behavioural model of pathological internet use concept, the current study evaluated the relationship between self-concept clarity, academic self-efficacy, perceived social support and GPIU among university students in Malaysia. A correlational research design was used to determine the correlation between the variables. A total of 480 undergraduate students aged between 20 and 24 were recruited in this study using the convenient sampling technique. Data were collected using self-administered survey questionnaires and established instruments of Self-Concept Clarity Scale, Academic Self-Efficacy Scale, Multidimensional Scale of Perceived Social Support and Generalised Problematic Internet Use Scale 2 to measure the aforementioned variables. Statistical Package for Social Science (SPSS) version 22.0 was employed to conduct reliability analysis, exploratory data analysis, univariate analysis, bivariate analysis and multivariate analysis. There was a significant association between self-concept clarity and GPIU. Respondents with a higher level of self-concept clarity had a lower tendency to get involved in GPIU. Furthermore, self-concept clarity was the strongest predictor for GPIU, followed by CGPA and number of hours spent on the Internet weekly. Undergraduates in Malaysia exhibited interest to imply rich information and social platform on Internet to improvise self-concept, rather than non-purposive usage of GPIU which need attention from related parties.